Implementasi Pendidikan Karakter melalui Budaya Sekolah di SMP Negeri 1 Teluk Keramat Kabupaten Sambas - Aldian Tomia; Syamsuri Syamsuri; Thomy Sastra Atmaja; Bistari Bistari; Shilmy Purnama (Journal on Education, 2024)
The research aims to identify and describe the implementation of character education through the school culture at SMP Negeri 1 Teluk Keramat in Sambas Regency. The researcher employed a qualitative descriptive research approach. The study involved students, the vice-principal, and civics education teachers as informants. Data collection methods used in this research encompassed observations, interviews, and document analysis. Data analysis in this study encompassed data reduction, data presentation, and drawing conclusions. The findings of this study reveal that character education through the school culture at SMP Negeri 1 Teluk Keramat in Sambas Regency is executed via various routine, spontaneous, exemplary, and conditioning activities. Routine activities consist of flag-raising ceremonies, recitation of prayers before and after lessons, Quranic readings before lessons, Quranic recitation sessions, class monitoring duties, and "Jum'at Bersih" (Clean Friday) activities, congregational Dhuhr prayers, and participation in extracurricular scouting activities. In these activities, students are instilled with nationalistic and religious values. Spontaneous activities include providing assistance to those affected by disasters, conducting random mobile phone checks, directly addressing students when they are not dressed neatly, addressing students directly when someone littered, and intervening when students are involved in fights. These activities promote social responsibility and discipline. Exemplary activities include maintaining the cleanliness of the school environment, punctuality of educational staff and students, using polite and respectful language, and starting lessons on time. These activities instill the value of discipline. Conditioning activities involve maintaining clean classrooms and teacher rooms, providing facilities that support character education implementation such as trash cans, handwashing stations, displayed vision and mission statements, information boards, green plants on school grounds and and others.